Overcoming barriers to the adoption of water-saving technologies in Jordan: policy pathways for transforming knowledge, attitudes and practices - Al-Zu’bi, Maha; Amdar, Nafn; Brouziyne, Youssef (International Water Management Institute, 2025)
Jordan faces severe water scarcity, worsened by rapid population growth, climate change, and overuse of limited groundwater. With per capita water availability at just 61 m³/year—well below the global threshold of 500 m³/year—Jordan is one of the most water-scarce countries. Agriculture, which consumes 48% of the country's freshwater, is particularly affected. The sector relies on inefficient irrigation, leading to low water productivity, especially in the highlands, where productivity is only JOD 0.36 per m³, much lower than the potential achievable with Water Saving Technologies (WSTs).Several challenges hinder the adoption of WSTs, including financial constraints, limited extension services, technical gaps, and unequal access, particularly for smallholders and marginalized communities. The lack of pre- and post-installation support from WST suppliers and extension services limits the effectiveness of these technologies. Without adequate guidance, many farmers struggle to integrate them into their farming practices, preventing full utilization. Therefore, aligning farmers’ knowledge, attitudes, and practices (KAP) with water conservation goals is essential for the successful adoption of WSTs. To address these challenges, research and tailored support are crucial. Researchers can identify obstacles to WST adoption, while practitioners can offer targeted support to overcome these issues. Policymakers can create policies that encourage WST adoption through financial incentives, education, and research. Education and awareness campaigns can help farmers understand the benefits of WSTs, while financial mechanisms, like subsidies or low-interest loans, can make these technologies more accessible.A farmer-centric approach is key to driving adoption. A Market Systems Development (MSD) strategy, which improves the entire market system surrounding WSTs, can promote wider adoption. Peer learning, where farmers share experiences and knowledge, can boost confidence in these technologies. Extension services play an important role by providing ongoing support and helping farmers adapt technologies to their needs. In conclusion, overcoming barriers to WST adoption and aligning farmers’ practices with water conservation goals is crucial for Jordan’s agricultural sustainability. With targeted education, financial support, and strong extension services, Jordan can ensure long-term water security and agricultural productivity.